Local Developers, Fragmented Development and Perils of Governance: Political Economy of Urban Land-grabbing in India - Gautam, Ajay K. (Economic and Political Weekly, 2025)
The incidence of land-grabbing by local developers, that leads to illegal colonies and unauthorised housing in the informal land markets of the National Capital Region, particularly in Gautam Buddha Nagar and Ghaziabad, is examined. The fieldwork reveals how developers exploit regulatory loopholes, collude with state actors, and leverage caste networks to gain control over land. This process fuels illegal colonies, marginalises lower-caste groups, and reshapes urban peripheries. The findings highlight the urgent need for governance reforms to curb speculative land dispossession and ensure equitable urban development in rapidly expanding Indian cities.
Keywords: Fragmented Development; Local Developers; Perils of Governance; Urban Land-Grabbing; Political Economy